Regulated Expression of PTPRJ by COX-2/PGE2 Axis in Endothelial Cells - Xu, Xiaobing; Lan, Wenya; Jin, Xinxin; Wang, Bin; Yan, Hongbo; Chen, Xi; Lai, Xiaowei; Zhang, Li; Zhang, Xiaohua; Li, Zhaoshen (PloS one, 2014)
This study was designed to examine a novel role of COX-2/PGE2 signaling as a regulator of PTPRJ expression in endothelial cells. A bioinformatics analysis of a whole genome array was carried out to search for regulators of PTPRJ expression in endothelial cells. PTPRJ expression was also measured in endothelial cells derived from a balloon injury-induced neointimal hyperplasia model in male New Zealand Rabbits. Changes in PTPRJ expression in HUVEC cells was examined by RT-PCR and western blotting after transfection of COX-2 plasmids or treatment with varying concentrations of a COX-2 inhibitor. A significant correlation was identified between COX-2 and PTPRJ in GSE39264 (Pearson correlation coefficient  =  -0.87; n = 22; P < 0.01, two-tailed). PTPRJ expression was reduced during the progression of neointimal hyperplasia after balloon injury, which correlated with an increase in COX-2 expression. In HUVECs, after transfection with 1 µg/ml, 0.5 µg/ml, or 0.25 µg/ml COX-2 plasmids, PTPRJ protein expression was reduced to 0.60- (± 0.08), 0.75- (± 0.09), and 0.88- (± 0.04) fold, respectively, while mRNA expression was reduced to 0.15- (± 0.03), 0.26- (± 0.05), and 0.47- (± 0.09) fold, respectively. After treatment of HUVECs with 10 µmol/L or 20 µmol/L celecoxib, the reduction in PTPRJ expression induced by COX-2 over-expression was not only rescued but in fact increased by 2.05-fold (± 0.28) and 3.34-fold (± 0.37), respectively, compared with control. Our results suggest that COX-2/PGE2 signaling may function as a negative regulator of PTPRJ expression in endothelial cells both in vivo and vitro.